The Art of The Gacha Lure: Determinants of The Continuous Use of Mobile Role-Playing Games (RPG) With Gacha System in Indonesia - Nyiayu Olivia Miranda Bakrie; Cellila Aditama; Lim Sanny (Yayasan Riset dan Pengembangan Intelektual (YRPI), 2024)
The expansion of the mobile games industry should be attributed to the convenience of in-game purchases that are adopted by most mobile games in the market. In this study, we aim to investigate the relationship between determinants of continuous use of mobile RPG games with gacha system in Indonesia. We disseminated a questionnaire that was then filled in by 257 respondents. From a total of 257 results, we excluded 38 questionnaires due to non-completion as well as 8 questionnaires due to the unreliability of questionnaire answers. There were 211 questionnaires remaining for the model analysis. We proposed a total of 13 hypotheses which resulted in flow experience and satisfaction being positively associated with intention of continuous use. The findings of this study highlight how massive the effect of different type of RPG games affect the determinants of players in Indonesia.